Pesticide Use Trends in the U.S.: Pesticides for Industrial/Commercial/Governmental Uses: PI-141/PI178, 1/2007 - Fishel, Frederick M. (EDIS, 2007)
This new series by Frederick M. Fishel provides data on volumes used and sales of pesticides from the latest EPA survey data available, 2001 - 2002. Published by the UF/IFAS Pesticide Information Office, January 2007.